Subleading power corrections to heavy quarkonium production in QCD factorization approach - Lee Kyle; Qiu Jian-Wei; Sterman George; Watanabe Kazuhiro (EPJ Web of Conferences, 2022)
We report the current understanding of heavy quarkonium production at high transverse momentum (pT) in hadronic collisions in terms of QCD factorization. In this presentation, we highlight the role of subleading power corrections to heavy quarkonium production, which are essential to describe the pT spectrum of quarkonium at a relatively lower pT. We also introduce prescription to match QCD factorization to fixed-order NRQCD factorization calculations for quarkonium production at low pT.